2017
DOI: 10.1158/1078-0432.ccr-17-0413
|View full text |Cite
|
Sign up to set email alerts
|

TOP2A and EZH2 Provide Early Detection of an Aggressive Prostate Cancer Subgroup

Abstract: Purpose Current clinical parameters do not stratify indolent from aggressive prostate cancer (PCa). Aggressive PCa, defined by the progression from localized disease to metastasis, is responsible for the majority of PCa-associated mortality. Recent gene expression profiling has proven successful in predicting the outcome of PCa patients, however they have yet to provide targeted therapy approaches that could inhibit a patient’s progression to metastatic disease. Experimental Design We have interrogated a tot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
69
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(79 citation statements)
references
References 49 publications
6
69
0
2
Order By: Relevance
“…Some studies have indicated that an elevated expression level of EZH2 might be potentially used as a biomarker for the diagnosis of prostate cancer. 38,39 Typically, the expression of EZH2 has been detected to be up-regulated in non-small-cell lung cancer, 40,41 which was consistent with the ndings in this study.…”
Section: Discussionsupporting
confidence: 89%
“…Some studies have indicated that an elevated expression level of EZH2 might be potentially used as a biomarker for the diagnosis of prostate cancer. 38,39 Typically, the expression of EZH2 has been detected to be up-regulated in non-small-cell lung cancer, 40,41 which was consistent with the ndings in this study.…”
Section: Discussionsupporting
confidence: 89%
“…Its enzyme is a marker of cell proliferation in normal and tumor tissue (28). TOP2A was confirmed to be involved in epigenetic regulation through enhancer of zeste homolog 2, and aberrant expression of TOP2A was correlated with malignant characteristics of prostate cancer (29,30). In the present study, TOP2A was upregulated in ACC compared with ACA according to microarray data, which was confirmed by RT-qPCR.…”
Section: Discussionsupporting
confidence: 74%
“…On the contrary, the predictive roles of MAD2L1 and ZWINT for LUADs have been reported [43,44]. Moreover, TOP2A (DNA topoisomerase II alpha) encodes a DNA topoisomerase which is a well-studied cancer-associated protein [45]. Several anticancer agents targeting DNA topoisomerase have been applied in clinical practice [46].…”
Section: Discussionmentioning
confidence: 99%